Meta-Analysis the Effect of Exclusive Breastfeeding on Anemia in Children Under Five - Azizah, Fikri Dian Dinu; Pamungkasari, Eti Poncorini; Murti, Bhisma (Journal of Maternal and Child Health, 2023)
Background: The prevalence of iron deficiency anemia is still high, especially in children under five. One effort to prevent iron deficiency anemia is exclusive breastfeeding for newborns. This study aims to analyze exclusive breastfeeding on the incidence of anemia in children under five. Subjects and Method: This study is a systematic review and meta-analysis, with PICO as follows: Population= toddlers aged <5 years; Intervention= exclusive breastfeeding; Comparison= non-exclusive breastfeeding; Outcome= iron deficiency anemia. The articles used in this study were obtained from several databases including PubMed, Springer Link, Science Direct, and Google Scholar, which were published from 2012 to 2022. The keywords to search for articles are as follows: "Children" AND ("exclusive Breastfeeding" OR "formula" OR "mixed feeding") AND (anemia OR "Iron deficiency"). The articles included in this study were full-text articles with a cross-sectional study design. Articles are collected using PRISMA flow diagrams. Articles were analyzed using the Review Manager 5.3 application. Results: A meta-analysis of 9 cross-sectional studies from Ethiopia, Taiwan, Bangladesh and China concluded that exclusive breastfeeding is effective in reducing the risk of anemia in children under five. Toddlers who are exclusively breastfed have a risk of developing anemia 0.55 times compared to those who are not exclusively breastfed, and the reduced risk is statistically significant (aOR= 0.55; 95% CI= 0.32 to 0.92; p= 0.020). Conclusion: Exclusive breastfeeding is effective in reducing the risk of anemia in children under five. Keywords: exclusive breastfeeding, anemia, toddlers. Correspondence: Fikri Dian Dinu Azizah. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A Surakarta 57126, Central Java, Indonesia. Email: fikridianda@gmail.com. Mobile: 081225002311.